2022
DOI: 10.3390/children9050743
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Huge Prevalence of Intracardiac Extension of Wilms Tumor—A Single Center Experience from a Ugandan Hospital

Abstract: Wilms tumor (WT) is the most common primary renal malignancy in young children. WT vascular extension to the inferior vena cava (IVC) occurs in 4–10% of cases and can reach the right atrium (RA) in 1%. Data on WT clinical presentation and outcome in developing countries are limited. The aim of the present study is to describe the prevalence of intracardiac extension in a consecutive population of WT patients observed in a large non-profit Ugandan hospital. A total of 16 patients with a histological diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Screening is therefore important for all categories of patients to limit disease-related morbidities and optimize care [19] . Our literature search revealed that only a few cases of intracardiac extension of WT have been reported in sub-Saharan Africa [9] , especially on the left side of the heart [11] . While the vena-caval extension of WT into the right atrium is a well-documented phenomenon, left atrial involvement is extremely rare [11] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Screening is therefore important for all categories of patients to limit disease-related morbidities and optimize care [19] . Our literature search revealed that only a few cases of intracardiac extension of WT have been reported in sub-Saharan Africa [9] , especially on the left side of the heart [11] . While the vena-caval extension of WT into the right atrium is a well-documented phenomenon, left atrial involvement is extremely rare [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Management of advanced WT is multi-disciplinary and multi-modal [10,17] . Neoadjuvant chemotherapy has been proven to reduce the size of the atrioventricular tumour, with complete regression of the intra-cardiac mass in some reports [9,10,[17][18][19] . Surgical management of intra-cardiac tumours is formidable and technically challenging, especially in LMICs [8][9][10]18] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations